Analysis of Teamwork, Organizational Culture, and Work Environment on Employee Job Satisfaction at PT Perkebunan Nusantara IV Regional I Medan - Izriyana; Abdi Setiawan; M. Chaerul Rizky (Yayasan Multidimensi Kreatif, 2024)
This study aims to find the influence of teamwork, organizational culture And work environment on employee job satisfaction PT Nusantara IV Plantation Region I Medan . The number of samples in this study was 65 respondents in the Human Resources and Management Systems section . This study used quantitative data processed with SPSS 25.0 with a multiple linear regression model. The results of the study showed that teamwork , organizational culture And work environment partially and simultaneously has a positive and significant effect on employee job satisfaction at PT Perkebunan Nusantara IV Regional I Medan . The results of the t-test show that teamwork has a regression value of 0.308, a calculated t value of 2.612 and a significance of 0.000. Organizational Culture has a regression value of 0.252, a calculated t value of 2.274 and a significance of 0.000. Work Environment has a regression value of 0.418 and a calculated t value of 3.461 . The results of the determination coefficient test of 89.4 % job satisfaction can be explained and obtained from the variables of teamwork, organizational culture And work environment while the remaining 10.6% is influenced by other factors.